Comparative Study of the Thermal Performance of Two Thermosiphon Solar Water Heaters System - Blaise Kamenan Koua; Paul Magloire Ekoun Koffi; Prosper Gbaha (International Journal of Renewable Energy Development, 2020)
The aim of this study is to present the comparative results of experimental investigations of the thermal performance of two thermosiphon solar water heaters system (SWHS). The first uses the coconut fiber (CF), a local vegetable and the second, the glass wool (GW), an imported and expensive material, as thermal insulations. The maximum instantaneous efficiencies are, respectively, 65.30 % and 58.7% with glass wool and coconut fiber while the mass flow rate values are, respectively, 0.0098 kg/s and 0.0078 kg/s with glass wool and coconut fiber. In addition, the calculated average values of F’(τα) and F’UL are, respectively, 0.79 and 5.86 Wm-2°C for the coconut fiber collector and 0.8 and 5.26 Wm-2°C for the glass wool collector. The average heat exchanger effectiveness obtained for the two SWHS are superior to 50%. As an environment-friendly and renewable material, coconut fiber is particularly suitable for thermal insulation in order to save energy. The experimental results show the ability of the constructed solar water heater in providing hot water suitable for maternity, hotels, households and encourage its implementation and utilization on a broad scale. The SWHS can be used in any weather conditions.